Alvogyl versus zinc oxide eugenol after saline irrigation as a treatment for alveolar osteitis - Khalifah, Mosaad (International Journal of Dental Research, 2018)
Background: Alveolar osteitis is one of the most common post-odontectomy complications. An agreement is lacking regarding the relative merits of various treatment methods. Of these treatments were alvogyl and Zinc oxide eugenol after saline irrigation.Objectives: The aim of the current study therefore was to evaluate the efficacy of both agents.Methods: A total of 987 patients were categorized into 4 groups (I, II, III, and IV) according to pain severity (mild, moderate, severe, or agonizing, respectively). Each group was randomly divided into two subgroups according treatment method: Alvogyl (Alv) and Zinc oxide eugenol following saline irrigation (I+Z).Results: Although, Alv was palliative in group. I, I+Z was curative in group, I and palliative in group II. Both agents were ineffective otherwise.Conclusion: The author recommends I + Z over alv.